2016
DOI: 10.1080/07448481.2015.1117466
|View full text |Cite
|
Sign up to set email alerts
|

A randomized intervention study to evaluate whether electronic messaging can increase human papillomavirus vaccine completion and knowledge among college students

Abstract: The intervention increased knowledge but not vaccine completion. More research with catch-up age populations is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 17 publications
1
89
1
Order By: Relevance
“…Of the 14 studies that did not find a positive improvement, all but one reported the intervention had a neutral effect on participants. Three of the studies found that despite the medical compliance reminders not being more effective than the control group, the reminders still had benefits, including increasing medical knowledge ( Richman et al, 2016 ), increasing self-efficacy in disease self-management ( Gatwood et al, 2016 ), and increasing the rate of consecutive days taking medication ( Stoner et al, 2015 ). Two of the studies reported being unpowered to find a statistically significant difference ( Boker et al, 2012 ; Buis et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 14 studies that did not find a positive improvement, all but one reported the intervention had a neutral effect on participants. Three of the studies found that despite the medical compliance reminders not being more effective than the control group, the reminders still had benefits, including increasing medical knowledge ( Richman et al, 2016 ), increasing self-efficacy in disease self-management ( Gatwood et al, 2016 ), and increasing the rate of consecutive days taking medication ( Stoner et al, 2015 ). Two of the studies reported being unpowered to find a statistically significant difference ( Boker et al, 2012 ; Buis et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not find that SMS reminder helped increase rate of Hepatitis B and anti-retroviral therapy (ART) medication adherence and, in fact, displayed lower rates of adherence than no reminder or treatment as usual (respectively) ( Linnemayr et al, 2017 ; McIver et al, 2016 ). Lastly, all studies that included a measure of feasibility and/or acceptability found positive results (e.g., Garofalo et al, 2016 ; Gengiah et al, 2014 ; Park et al, 2014 ), even if the intervention was not found to be statistically significant (e.g., Buis et al, 2017 ; Richman et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19] Interventions targeting college students have been successful in briefly, yet sustainably, delivering information designed to increase HPV knowledge and intentions to become vaccinated. [20][21][22][23][24][25] Very few of these interventions study the potential impact of HPV education on knowledge and vaccine attitudes among Hispanic or ethnically diverse college students.…”
Section: Purposementioning
confidence: 99%
“…The systematic search conducted on November 12, 2018 yielded 3013 unique titles, from which 81 full texts were screened. Nine studies, eight peer-reviewed publications and one doctoral dissertation, involving 9749 participants were included ( Chao et al, 2015 , DiClemente et al, 2015 , Joseph et al, 2016 , Kim, 2017 , Lee et al, 2018 , Parra-Medina et al, 2015 , Reiter et al, 2018 , Richman et al, 2016 , Winer et al, 2016 ). For the doctoral dissertation, the full text was obtained through email contact with the author ( Kim, 2017 ), after screening a related conference abstract returned in the systematic search ( Kim et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were published from 2015 to 2018 and all were conducted in the United States. The majority of studies employed a randomized study design (88.9%; n = 8/9) ( Chao et al, 2015 , DiClemente et al, 2015 , Joseph et al, 2016 , Kim, 2017 , Lee et al, 2018 , Reiter et al, 2018 , Richman et al, 2016 , Winer et al, 2016 ). The target populations for HPV vaccination ranged in age from nine to 26 years.…”
Section: Resultsmentioning
confidence: 99%